Teachers' understanding on brain-based teaching and learning approach in mathematics classroom - Saifulbahri, Bin Hj. Abdul Rahman (Universiti Malaysia Sarawak, UNIMAS, 2014)
The emergence of TIMMS and PISA that measure the student cognitive performance against the international standards has become very important and the latest TIMMS and PISA result showed that critically 18% and 60% of the students did not meet minimum proficiency level in Mathematics. These students were identified as possessing only limited mastery of basic mathematical and scientific concepts. The new education policy has been designed to meet the standard and the teachers and pupils have to equip with new approach of teaching and learning method. Nevertheless, to ensure the students in primary school are equipped with the skills above, there must be a suitable instructional or suitable teaching and learning method to accommodate the demand. Brain-based learning is the one that can be proposed to be implemented by the teacher in the classroom. Brain based learning involves taking what we know about the brain, its development, its learning and combining the factors in the intelligent way to connect and excites the students’ learning. The implementation will be based on the twelve brain based learning principle promoted by Caine (2005) in order to facilitate learning and prepare the children towards 21st century. Hence, this study used qualitative approach through open-ended survey questionnaire by means of Facebook, electronic mail (e-mail), and educational portal and also interview to explore teachers understanding of the brain-based learning in the learning of the Mathematics and identify the potential of implementing the brain-based learning in the classroom. The samples consists of 30 mathematics primary school teachers purposively selected where 20 samples were from online open-ended survey questionnaire by using Google form and remaining 10 of the samples were collected from the one primary school in Padawan Division through the semistructured interview and open-ended survey questionnaire form. The findings for this study discovered mathematics teachers’ lack of understanding on Brain-based learning. However, their educational practices and beliefs showed that there were potentials in implementing the brain-based learning in mathematics classroom.